2022
DOI: 10.3390/antibiotics11020278
|View full text |Cite
|
Sign up to set email alerts
|

Perspective, Opportunities and Challenges in Using Fennel (Foeniculum vulgare) in Poultry Health and Production as an Eco-Friendly Alternative to Antibiotics: A Review

Abstract: Following the European Union’s restriction on antibiotic growth promoters, research on enhancing gut health has been accelerated. As the poultry industry is facing issues that were previously managed by antimicrobial growth promoters, the hunt for the best remedies continues to find suitable alternatives. Simultaneously, social pressure is mounting to reduce the usage of antibiotics and replace them with other feed additives. Consumers believe a number of accessible options to be safe, with phytogenics playing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…While the current results not agreement with (14 and 31), who reported were no significant differences in percentage of yolk weight when adding Fennel seeds or extracts to laying hens' diets. The reason for the decrease in weight of yolk can be attributed to the fact that it is known that the yolk is the most part of the egg that contains fat, and since the increase in the amount of Fennel in the diet negatively affects the amount of fat in the egg, especially the yolk, so the percentage of yolk weight will decrease with a decrease in the percentage of fat in the yolk, this is what was shown by the results of the chemical analysis of egg yolk in Table 4, which indicates a decrease in the percentage of fat in the yolk with an increase in the percentage of Fennel seeds powder (15). Yolk Weight: Table 5 showed the effect of adding different percentages of Fennel seeds powder to laying hens' diets on weight of yolk, as the results were significant (P≤0.05) differences in weight of yolk between the different treatments, it was observed that there was a significant decrease in weight of yolk in favor of treatment T6, as the weight of the yolk was 14.7 g, which did not differ significantly with treatment T5 15.3 g when compared with the rest of the experiment treatments.…”
Section: Resultsmentioning
confidence: 79%
“…While the current results not agreement with (14 and 31), who reported were no significant differences in percentage of yolk weight when adding Fennel seeds or extracts to laying hens' diets. The reason for the decrease in weight of yolk can be attributed to the fact that it is known that the yolk is the most part of the egg that contains fat, and since the increase in the amount of Fennel in the diet negatively affects the amount of fat in the egg, especially the yolk, so the percentage of yolk weight will decrease with a decrease in the percentage of fat in the yolk, this is what was shown by the results of the chemical analysis of egg yolk in Table 4, which indicates a decrease in the percentage of fat in the yolk with an increase in the percentage of Fennel seeds powder (15). Yolk Weight: Table 5 showed the effect of adding different percentages of Fennel seeds powder to laying hens' diets on weight of yolk, as the results were significant (P≤0.05) differences in weight of yolk between the different treatments, it was observed that there was a significant decrease in weight of yolk in favor of treatment T6, as the weight of the yolk was 14.7 g, which did not differ significantly with treatment T5 15.3 g when compared with the rest of the experiment treatments.…”
Section: Resultsmentioning
confidence: 79%
“…Phytogenic feed additives considerably impact the gut environment, either directly or indirectly (Khan et al, 2022). In this study, the effect of the studied phytogenic herbs was found to be very effective in improving the performances of broiler chickens and exhibiting antimicrobial activities.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, following the European Union’s restriction on antibiotic growth promoters, research on enhancing gut health has been accelerated [ 6 ]. With the poultry industry facing issues previously controlled by antimicrobial growth promoters, the search for suitable alternatives has continued.…”
mentioning
confidence: 99%
“…With the poultry industry facing issues previously controlled by antimicrobial growth promoters, the search for suitable alternatives has continued. In their next review, Khan et al [ 6 ] describe how the use of fennel seeds ( Foeniculum vulgare ) could be beneficial for poultry. The physicochemical and biological properties of F. vulgare are discussed, as well as the diverse chemical composition of the plant.…”
mentioning
confidence: 99%
See 1 more Smart Citation